Thực trạng hoạt động giáo dục hướng nghiệp cho học sinh ở một số trường trung học cơ sở huyện Thanh Trì, thành phố Hà Nội - Phạm, Thị Nhung; Nguyễn, Thị Ngọc Bé (Tạp chí Giáo dục, 2025)
Vocational education activities for students in schools are critical. Vocational education activities not only help students identify career interests and motivations for choosing a career but also give students the right direction in choosing a career, thereby helping students fully develop their strengths and abilities and develop creativity in the career they choose. The article analyzes the current status of vocational education activities for students in some secondary schools in Thanh Tri district, Hanoi city according to the approach of educational components. The survey showed that the vocational educational activities were carried out quite regularly and the results achieved were at a good level. However, this activity still has many limitations: such as teachers' ability in organizing activities not being high, the implementation content needing to be more diverse, the coordination of methods not being flexible, and the assessment of educational results needing to be more comprehensive. The research results will be an essential practical basis for proposing measures to improve the effectiveness of vocational education activities for students.